Targeting multiple cancers: exploring the potential role of stem cells in treating 10 distinct types - Munawar Ali; Syeda Areej Imran; Hafiza Malaika Choudhary; Laiba Batool; Amna Amin; Muhammad Umair Aslam; Hafiz Muhammad Sultan (Journal of Current Oncology and Medical Sciences)
Stem cell research has gained significant prominence due to its therapeutic potential in addressing diseases that are difficult to treat with conventional therapies, particularly cancer. Cancer remains a global health crisis responsible for one in six deaths worldwide and is characterized by uncontrolled cell growth, metastasis, and a generalized loss of growth control. Traditional cancer treatments, including surgery, radiation, and chemotherapy, have limitations, such as damaging healthy cells and tissues, and are often associated with cancer recurrence and metastasis. In response to these challenges, stem cell technology has emerged as a promising frontier, offering novel approaches to target and eliminate cancer cells while potentially reducing the side effects associated with conventional therapies. This review explores the biochemical properties of stem cells and their potential applications in treating ten distinct types of cancer. We analyze each cancer type to understand the potential use of stem cells in treatment. The article aims to contribute the growing body of knowledge and provide insights into the future directions of stem cell research in oncology.